2017
DOI: 10.1093/ndt/gfx210
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischaemic preconditioning for renal and cardiac protection in adult patients undergoing cardiac surgery with cardiopulmonary bypass: systematic review and meta-analysis of randomized controlled trials

Abstract: RIPC did not consistently reduce morbidity and mortality in adults undergoing cardiac surgery with CPB. In the subgroup on volatile anaesthetics only, RIPC markedly and significantly reduced the incidence of AKI and composite endpoint as well as myocardial injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 68 publications
0
24
0
Order By: Relevance
“…The potential interaction between anaesthetic regimen and the effect of RIPC is debatable. Results from meta-analyses and clinical studies are contradictory and primarily from cardiac surgery 29303536. To the best of our knowledge, no clinical trial has specifically investigated the influence of an anaesthetic regimen on the effect of RIPC.…”
Section: Discussionmentioning
confidence: 99%
“…The potential interaction between anaesthetic regimen and the effect of RIPC is debatable. Results from meta-analyses and clinical studies are contradictory and primarily from cardiac surgery 29303536. To the best of our knowledge, no clinical trial has specifically investigated the influence of an anaesthetic regimen on the effect of RIPC.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the long-term effects of repetitive weekly bursts of subclinical injury in individuals practicing high-intensity exercises are unknown. However, it is also possible that some individuals may develop improved resilience to renal insults, as observed with remote ischemic preconditioning preventing AKI, which enhanced the renal recovery in patients with AKI and reduced the long-term incidence of major adverse kidney events in high-risk patients undergoing cardiac surgery [ 41 ]. Likewise, acute exercise or continuous training schedules may induce or activate heat shock proteins, a group of proteins that is crucial in the preservation of protein and cell homeostasis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently performed large meta-analyses demonstrated that postoperative cardiac biomarker concentrations were lower in cardiac surgery patients after RIPC. [14][15][16] To date, a cardioprotective effect of RIPC was not observed in patients undergoing major abdominal surgery. A previous randomized trial with RIPC in abdominal surgery patients (>90% of patients underwent colon surgery) found no differences in hs-cTnT concentrations until 72 hours after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A possible interference of propofol with the cardioprotective effects of RIPC, which has been extensively described in prior studies, was ruled out by our study design. 14,[16][17][18] Surgical tissue injury triggers pro-and anti-inflammatory pathways. An excessive activation of the immune system, as reflected by high concentrations of IL-6, has been associated with adverse .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation